Architecture proposal for a support system to upper limb telerehabilitation by capturing biomechanical signals - Callejas-Cuervo, Mauro; Vélez-Guerrero, Manuel Andrés; Ruíz-Olaya, Andrés Felipe; Gutiérrez-Salamanca, Rafael María (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This article proposes a system for Telerehabilitation of people with motor disorders of the upper limb, by making a literature review about works related with the provision of the physical therapy service with ICT’s use. Likewise, there is a brief description of the modules integrating the system: motion capture system based on inertial sensors and motion capture with camera, joint angle estimator was implemented through Kalman filter, IT app which registers the electronic medical record and finally, the active videogames module.